An Advanced Coupling Complexity Metric for Evaluating the Quality of OO Software Modules - Ravi, T.N; Vijayaraj, N (International Journal of Computer Sciences and Engineering, 2018)
Software metrics plays a major role in assessing the quality of software in testing process. Software metrics elucidates the complexity, reusability, maintainability and understandability of the software code. Software complexity metrics are one of the emerging types of software metrics that focuses on the cognitive analysis of software in terms of understandability and maintainability. In other words, it can be rephrased as the effort taken to comprehend the program code for future enhancements. Complexity metrics has a direct impact with the analysis of complexity in software through an intrinsic study on the object oriented features. This paper proposes a novel Coupling Complexity Metric (IMFC), to highlight the complexity that incurs with coupling and weighs the complexity of a class.